EFFECTIVENESS OF VILLAGE FUND POLICY FOR ECONOMIC DEVELOPMENT AND RURAL INFRASTRUCTURE IN SIANTAR DISTRICT SIMALUNGUN REGENCY - Silitonga, Hery Pandapotan; Sianipar, Ruth Tridiyanti; Sembiring, Lenny Dermawan; Putri, Juan Anastasia; Siregar, Robert Tua (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2022)
The purpose of this study is to determine the use of village funds has been effective in developing rural economy and infrastructure development in Siantar District Simalungun Regency. Qualitative research methods used in this study, the data analysis techniques used qualitative descriptive data analysis techniques. The results of the study obtained by respondents stated that village funds distributed from the government are sufficient for development in the village, the existence of village funds is very helpful for village development, the largest use of village funds used for the construction and maintenance of agricultural business roads, and in community empowerment the largest village funds are used for village government programs for village community empowerment,Â The village government compiles planning documents consisting of APBDes, RPJMDes, and RKPDes, each planning program must be supported by the village community in implementation by informing every expenditure and income of funds, supervision of monitoring periodically related to the physical development of the village, and the submission of reports on the use of village funds used for village development needs to be delivered transparently